Bindungsgrenzen Überlange Mindestvertragslaufzeiten und die objektiven Freiheiten der Zivilrechtsordnung - Hogrebe, Ludwig (Mohr Siebeck, 2018)
The binding limits of German private law mediate between the freedom from attachment and the freedom to bind. Protection from unlimited attachment is a patchy and random affair, yet the very existence of binding limits reveals the idea of a civil social order.
PublicationDate: 20180511
Keywords: Dauerschuldverhältnis -- Internationale Insolvenzanfechtung -- Pfändungsbeschränkung -- Kündigungsausschluss -- Amerikanische Revolution -- U.S. Supreme Court -- Bindungsfreiheit -- Ewige Verträge -- Zeit und Rechte -- Rechtsgeschichte -- Rechtstheorie -- Bürgerliches Recht